Participação escolar na formação da ética e da cidadania - Schmidt, Felipe [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
This research originated from a project entitled Be Better, which took place from the observation of the school environment and postures, as indiscipline, prejudice, among others, that influence behavior, development and, consequently, the performance school students. Aspects to social life, such as bullying, intolerance to personal differences, customs, cultures and habits were also observed. Looking for ways to contribute to the training of students and minimize these problems, it carried out the project in question, through weekly meetings, in order to verify how the approach used in these meetings contributed to the formation of citizenship and ethical values, and to improve the social life of the participating students. These students, in this study were high school students, aged between 15 and 18, a private school located in a city in Paraíba Valley region. To perform such project, activities were conducted on various topics, in turn against classes with students who are interested in participating. They were involved for various reasons, but with the common purpose to meet different opinions on the topics, thus opening the door to the understanding of individual differences, tolerance and improvement of social life. Data from this study were made from the transcript of interviews with 13 project participants students. The data analysis showed that the participation of the subjects in the project in question had a positive impact on these students lives, providing personal growth, to accept the changes, breaking prejudice and tolerance of differences; improvement in social life, both in and outside school, with parents, classmates and others; more active participation in social issues and concern for the collective. These results indicate that the approach used in meetings contributed to the formation of citizenship and ethical values of the subjects

Este trabalho de pesquisa foi originado de um projeto, intitulado Ser Melhor, que ocorreu a partir da observação do ambiente escolar e de posturas inadequadas, como indisciplina, preconceitos, dentre outras, que influenciam no comportamento, desenvolvimento e, consequentemente, no desempenho escolar dos estudantes. Aspectos associados ao convívio social, tais como Bullying, intolerância às diferenças pessoais, de costumes, culturas e hábitos também foram observados. Buscando meios para contribuir para a formação dos alunos e minimizar esses problemas, foi realizado o projeto em questão, mediante encontros semanais, com o intuito de se verificar de que forma a abordagem usada nesses encontros contribuiu para a formação da cidadania e de valores éticos, bem como para a melhoria do convívio social dos alunos participantes. Esses alunos, sujeitos desta pesquisa, eram estudantes do Ensino Médio, na faixa etária entre 15 e 18 anos, de uma escola privada, localizada em uma cidade da região do Vale do Paraíba. Para a realização de tal projeto, foram desenvolvidas atividades sobre temas variados, no contra turno das aulas, com os alunos que se interessaram em participar. Eles se envolveram por diversas razões, porém com o intuito comum de conhecer diferentes opiniões sobre os temas abordados, abrindo assim as portas para a compreensão das diferenças individuais, da tolerância e a melhoria do convívio social. Os dados desta pesquisa foram constituídos pela transcrição das entrevistas realizadas com 13 alunos participantes do projeto. A análise desses dados mostrou que a participação no projeto em questão teve um impacto positivo na vida desses alunos, propiciando crescimento pessoal, no sentido de aceitação às mudanças, quebra de preconceitos e tolerância às diferenças; melhoria no convívio social,... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Ética estudantil; Ambiente escolar; Cidadania; Student ethics